PENYELESAIAN SENGKETA TANAH ULAYAT ANTARA MASYARAKAT ADAT SENAMA NENEK DENGAN PTPN V DI KENEGERIAN SENAMA NENEK KECAMATAN TAPUNG HULU KABUPATEN KAMPAR PROVINSI RIAU - AL JAMIL FEBRIADI (PREMISE LAW JURNAL, 2017)
Customary Institution of Ninik Mamak (Tribal Leader) is the representative of customary community in One Lineage Community, Tapang Hulu Subditrict, Kampar Regency, Riau Province which is expected to be able to settle the dispute over communal reserved land that has been going since 1996. The administration and responsibility of communal reserved land, in Kampar Regency, Riau Province; is usually taken care of a Customary Institution called Ninik Mamak of its community. Therefore, it is necessary to study the settlement of the dispute over communal reserved land between customary One Lineage community and PTPN V in Customary One Lineage Community at Tapung Hulu Subdistrict, Kampar Regency, Riau Province. The research problems are: How the role of Customary Institution of One Lineage Community is to settle the dispute over communal reserved land between customary One Lineage community and PTPN V; How the dispute over communal reserved land between customary One Lineage community is settled; and how the status of the communal reserved land which was earlier possessed by PTPN V.This is an empirical juridical research with descriptive approach. The data were collected through library study, analyzed qualitatively which describes and analyzes simultaneously the research problem. Deductive-inductive reasoning method is used to draw a conclusion.Keywords: Communal Reserved Land, Settlement, Customary Community